The Role of Skin and Orogenital Microbiota in Protective Immunity and Chronic Immune-Mediated Inflammatory Disease - Park, Young Joon; Lee, Heung Kyu (Frontiers in Immunology, 2018)
The skin and orogenital mucosae, which constitute complex protective barriers against infection and injuries, are not only the first to come into contact with pathogens but are also colonized by a set of microorganisms that are essential to maintain a healthy physiological environment. Using 16S ribosomal RNA metagenomic sequencing, scientists recognized that the microorganism colonization has greater diversity and variability than previously assumed. These microorganisms, such as commensal bacteria, affect the host’s immune response against pathogens and modulate chronic inflammatory responses. Previously, a single pathogen was thought to cause a single disease, but current evidence suggests that dysbiosis of the tissue microbiota may underlie the disease status. Dysbiosis results in aberrant immune responses at the surface and furthermore, affects the systemic immune response. Hence, understanding the initial interaction between the barrier surface immune system and local microorganisms is important for understanding the overall systemic effects of the immune response. In this review, we describe current evidence for the basis of the interactions between pathogens, microbiota, and immune cells on surface barriers and offer explanations for how these interactions may lead to chronic inflammatory disorders.